Intra-articular facet joint injections for low back pain: a systematic review - Vekaria, Rajni; Bhatt, Ree’thee; Ellard, David R.; Henschke, Nicholas; Underwood, Martin; Sandhu, Harbinder (European spine journal, 2016)
Evidence supporting the use of therapeutic intra-articular facet joint injections for patients with suspected facet joint pain is sparse. A systematic review including a narrative synthesis was carried out to determine if intra-articular facet joint injections with active drug are more effective in reducing back pain and back pain-related disability than a sham procedure or a placebo/inactive injection. Secondly, to determine if intra-articular facet joint injections with active drug or placebo/inactive injection are more effective in reducing back pain and back pain-related disability than conservative treatment.
Gesehen am 04.06.2020